Spinal injury rates and specific causation in motor vehicle collisions. (June 2023) - Kent, Richard; Cormier, Joseph; McMurry, Timothy L.; Johan Ivarsson, B.; Funk, James; Hartka, Thomas; Sochor, Mark
Highlights: National estimates of spinal injuries are reported. Spinal injuries caused by an MVC are relatively rare (511 injured occupants per 10, 000 exposed to an MVC), which is consistent with the biomechanical forces required to generate injury. Spinal injury rates increase as impact severity increases, and fractures are more common in higher-severity exposures. The rate of sprain/strain in the cervical spine is greater than in the lumbar spine. Disc injuries are extremely rare in MVCs (0.01 occupants per 10, 000 exposed) and typically occur with concomitant trauma, which is consistent with biomechanical testing. Abstract: Motor vehicle collisions (MVCs) are a leading cause of acute spinal injuries. Chronic spinal pathologies are common in the population. Thus, determining the incidence of different types of spinal injuries due to MVCs and understanding biomechanical mechanism of these injuries is important for distinguishing acute injuries from chronic degenerative disease. This paper describes methods for determining causation of spinal pathologies from MVCs based on rates of injury and analysis of the biomechanics require to produce these injuries. Rates of spinal injuries in MVCs were determined using two distinct methodologies and interpreted using a focused review of salient biomechanical literature. One methodology used incidence data from the Nationwide Emergency Department Sample and exposure data from the Crash Report Sample System supplemented with a telephone survey to estimate total national exposure to MVC. The other used incidence and exposure data from the Crash Investigation Sampling System. Linking the clinical and biomechanical findings yielded several conclusions. First, spinal injuries caused by an MVC are relatively rare (511 injured occupants per 10, 000 exposed to an MVC), which is consistent with the biomechanical forces required to generate injury. Second, spinal injury rates increase as impact severity increases, and fractures are more common in higher-severity exposures. Third, the rate of sprain/strain in the cervical spine is greater than in the lumbar spine. Fourth, spinal disc injuries are extremely rare in MVCs (0.01 occupants per 10, 000 exposed) and typically occur with concomitant trauma, which is consistent with the biomechanical findings 1) that disc herniations are fatigue injuries caused by cyclic loading, 2) the disc is almost never the first structure to be injured in impact loading unless it is highly flexed and compressed, and 3) that most crashes involve predominantly tensile loading in the spine, which does not cause isolated disc herniations. These biomechanical findings illustrate that determining causation when an MVC occupant presents with disc pathology must be based on the specifics of that presentation and the crash circumstances and, more broadly, that any causation determination must be informed by competent biomechanical analysis.